The Study of Selection of Coal-Fired Supplier in Thermal Power Enterprise Based on the Extension Analysis Method - Tiejun Ci; Xiyang Liu (Institute of Advanced Engineering and Science, 2013)
Electric power market competition is intense. The competition between the various power plants will is the contest of economic efficiency as the core. Fuel cost is the center link of production management and economic accounting in thermal power plant, so selection management of the coal-fired supplier has great significance for the development of thermal power enterprise and improvement of the economic benefits. The paper constructs evaluation index system of coal-fired supplier, using the AHP method to determine the weight of evaluation index, and comprehensively evaluating to the coal-fired supplier with correlation functions in the extenics. The result indicates that it applies combination of the AHP and the extension analysis method to the selection of coal-fired supplier, which can accurately reflect relative importance of evaluation index, and directly reflect the detailed situation of supplier. This method is scientific, reliable and practical, which is applicable for various comprehensive evaluations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2837